Epidemiology and risk factors of respiratory syncytial virus associated acute respiratory tract infection in hospitalized children younger than 5 years from Sri Lanka - Divarathna, Maduja V. M.; Rafeek, Rukshan A. M.; Morel, Adrian J.; Aththanayake, Chathuri; Noordeen, Faseeha (Frontiers in Microbiology, 2023)
Background: Respiratory syncytial virus (RSV) is the leading cause of acute respiratory tract infections (ARTI) and a major cause of morbidity and mortality in children worldwide. Aim: This study aimed to describe the prevalence and seasonal patterns of RSV and to determine the actual and predictive association of RSV-associated ARTI and clinical, sociodemographic, and climatic risk factorsin children <5 years. Methods: Nasopharyngeal aspirates were collected from 500 children <5 years admitted to the Kegalle General Hospital, Sri Lanka between May 2016 to July 2018. RSV and RSV subtypes were detected using immunofluorescence assay and real time RT-PCR, respectively. Descriptive and inferential statistics were done for the data analysis using Chi-square, Fisher's exact, Kruskal-Wallis test, and multiple binary logistic regression in the statistical package for social sciences (SPSS), version 16.0. Results: Prevalence of RSV-associated ARTI was 28% in children <5 years. Both RSV subtypes were detected throughout the study period. RSV-B was the dominant subtype detected with a prevalence of 72.14%. RSV infection in general caused severe respiratory disease leading to hypoxaemia. Compared to RSV-B, RSV-A infection had more symptoms leading to hypoxaemia. Factors increasing the risk of contracting RSV infection included number of people living (n>6), having pets at home and inhaling toxic fumes. The inferential analysis predicts RSV infection in children <5 years with ARTI, with a 75.4% probability with clinical and socio-demographic characteristics like age <1 year, fever for >4 days, cough, conjunctivitis, stuffiness, fatigue, six or more people at home, having pets at home and inhaling toxic fumes. Climatic factors like increases in temperature ( o C), wind speed (Km/hr), wind gust (Km/hr), rainfall (mm) and atmospheric pressure (mb) showed a strong correlation with the RSV infection in children.